Changes in Lifestyle and Eating Habits of the Libyan Population During the COVID-19 Pandemic - F. El-Mani, Souad; Eltuhami, Ashmisa; M. Mansour, Reima; Elabbar, Laila; Bosrewill, Noha; Burwag, Shams; Alfadil, Malak; Elabbar, Wafa (Libyan Journal of Public Health Practices, 2024)
The corona virus pandemic has had a massive impact on people globally. Due to national lockdowns and social distancing people all over the world have developed irregular lifestyles. The current study aimed to assess the lifestyle and eating habit changes of population during the COVID-19 pandemic. A cross-sectional study was conducted by random sampling (N =940) on the general population of the Libyan population during the period from February 9th, 2021 until March 15th, 2021. A questionnaire was used to assess the changes of lifestyle and eating habits during COVID-19, which later identified by analysis using the SPSS program. The majority of the respondents 81% were not infected with the corona virus, and less than half of them, 39% followed all the recommended procedures. To lower the risk of being infected there was an increase in supplement use among female participants in comparison to male participants (85% of female vs. 15%, male p.value =0.000). This study also indicated that most of participants had a sedentary life style and changes in eating habits. These changes were seen more among participants infected with corona virus than others who were not infected (51% vs. 45%, p=0.000). The current study concluded that there were changes in participants’ life style during the COVID-19 pandemic; the majority of the participants had a sedentary lifestyle, and increase in their body weight and in meal consumption- especially during the evening Education programs should be conducted to promote healthy lifestyle and healthy eating to combat infections such as COVID-19.